Using the five senses of success framework to understand the experiences of midwifery students enroled in an undergraduate degree program. Issue 1 (January 2015) - Sidebotham, M.; Fenwick, J.; Carter, A.; Gamble, J.
Abstract Background developing a student׳s sense of capability, purpose, resourcefulness, identity and connectedness (five-senses of success) are key factors that may be important in predicting student satisfaction and progression within their university program. Aim the study aimed to examine the expectations and experiences of second and third year midwifery students enroled in a Bachelor of Midwifery program and identify barriers and enablers to success. Method a descriptive exploratory qualitative design was used. Fifty-six students enroled in either year 2 or 3 of the Bachelor of Midwifery program in SE Queensland participated in an anonymous survey using open-ended questions. In addition, 16 students participated in two year-level focus groups. Template analysis, using the Five Senses Framework, was used to analyse the data set. Findings early exposure to 'hands on' clinical midwifery practice as well as continuity of care experiences provided students with an opportunity to link theory to practice and increased their perception of capability as they transitioned through the program. Student׳s sense of identity, purpose, resourcefulness, and capability was strongly influenced by the programs embedded meta-values, including a 'woman centred' approach. In addition, a student׳s ability to form strong positive relationships with women, peers, lecturers and supportive clinicians was central to developing connections and ultimately a sense of success. A sense of connection not only fostered an ongoing belief that challenges could be overcome but that students׳ themselves could initiate or influence change. Conclusions the five senses framework provided a useful lens through which to analyse the student experience. Key factors to student satisfaction and retention within a Bachelor of Midwifery program include: a clearly articulated midwifery philosophy, strategies to promote student connectedness including the use of social media, and further development of clinician׳s skills in preceptorship, clinical teaching and facilitation. Program delivery methods and student support systems should be designed to enable maximum flexibility to promote capability and resourcefulness and embed sense of purpose and identity early in the program.